Imperial bedlam : institutions of madness in colonial southwest Nigeria - Sadowsky, Jonathan Hal. (Berkeley : University of California Press, 1999)
This historical study examines primary source material, writings by African patients in these institutions and the reports of officials, doctors, and others, to discuss the meaning of madness in Nigeria, the development of colonial psychiatry, and the connections between them. This book follows the development of insane asylums from their origins in the nineteenth century to innovative treatment programs developed by Nigerian physicians during the transition to independence. Special attention is given to the writings of those considered "lunatics," a perspective relatively neglected in previous studies of psychiatric institutions in Africa and most other parts of the world.
1. Introduction -- 2. The Nineteenth Century: From Pity to Alarm -- 3. Material Conditions and the Politics of Care -- 4. "Proper Subjects for Confinement" -- 5. The Confinements of Isaac O.: A Case of "Acute Mania" -- 6. Psychiatry and Colonial Ideology -- 7. Conclusion.
Includes bibliographical references (pages 119-166) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Psychiatric hospitals -- Nigeria -- History; Mentally ill -- Care -- Nigeria -- History; Mental illness -- Treatment -- Nigeria -- History; Psychiatry -- Nigeria -- History; Imperialism -- Health aspects -- Nigeria -- History; Nigeria -- Colonial influence -- Health aspects -- History; Nigeria -- Colonization -- Health aspects -- History; Hospitals, Psychiatric -- history; Colonialism; Nigeria; Personnes vivant avec un trouble de santé mentale -- Soins -- Nigeria -- Histoire; Maladies mentales -- Traitement -- Nigeria -- Histoire; PSYCHOLOGY -- Mental Health; PSYCHOLOGY -- Mental Illness; MEDICAL -- Mental Health; HISTORY / Africa / General; Colonial influence -- Health aspects; Colonization -- Health aspects; Imperialism -- Health aspects; Mental illness -- Treatment; Mentally ill -- Care; Psychiatric hospitals; Psychiatry; Nigeria; Kolonialismus; Psychiatrische Versorgung; Nigeria -- Südwest; Koloniaal bestuur; Psychiatrische inrichtingen; Nigeria (Südwest); History